Reactive arthritis secondary to Hafnia alvei enterocolitis - Erre, Gian Luca (BMJ Case Rep, 2019)
Diagnosis of postenteritic reactive arthritis (ReA) is a challenge and might have a broad range of differential diagnoses. A 50-year-old man was referred to our attention because of persistent inflammatory low back pain and asymmetric oligoarthritis. The clinical history was positive for diarrhoea in the previous 3 months. Inflammatory bowel disease, Whipple and celiac diseases were carefully excluded. In addition, serology, stool cultures, biopsies from the upper gastrointestinal tract yielded negative results for infections. A presumptive diagnosis of ReA was done and a non-steroidal anti-inflammatory drug trial prescribed. Persistence of symptoms prompted us for a second look of the colon. Biopsy collected from the terminal ileum were cultured and surprisingly colonies of Hafnia alvei, a rod-shaped Enterobacteriaceae, were detected. Treatment with ciprofloxacin leads to fast symptoms resolution. Although enterocolitis from H. alvei has been rarely reported, the culture of intestinal specimens might be recommended in the work-up of patients with suspected postenteritic ReA.